Actin Alpha 2 (ACTA2) Downregulation Inhibits Neural Stem Cell Migration through Rho GTPase Activation. (16th May 2020) - Zhang, Ji; Jiang, Xuheng; Zhang, Chao; Zhong, Jun; Fang, Xuanyu; Li, Huanhuan; Xie, Fangke; Huang, Xiaofei; Zhang, Xiaojun; Hu, Quan; Ge, Hongfei; Yu, Anyong
Abstract : Although neural stem cells (NSCs) could migrate towards lesions after central nervous system (CNS) injury, the migration ability always is restricted due to the disturbed composition and density of the adhesion ligands and extracellular matrix (ECM) gradient after CNS injury. To date, various methods have been developed to enhance NSC migration and a number of factors, which are affecting NSC migration potential, have been identified. Here, primary NSCs were cultured and the expression of actin alpha 2 (ACTA2) in NSCs was determined using reverse transcription polymerase chain reaction (RT-PCR) and immunostaining. Next, the role of ACTA2 in regulating NSC migration and the potential mechanism was explored. Our results demonstrated that ACTA2 expressed in NSCs. Meanwhile, downregulated ACTA2 using siRNA inhibited NSC migration through hindering actin filament polymerization via increasing RhoA expression and decreasing Rac1 expression. The present study might enrich the basic knowledge of ACTA2 in NSC migration and open an avenue for enhancing NSC migration potential, subsequently providing an intervention target for functional recovery after CNS injury.